Recombinant human PDGF-BB in foot and ankle fusion. (March 2012) - DiGiovanni, Christopher W; Lin, Sheldon; Pinzur, Michael
Autogenous bone graft (autograft) is currently the gold standard for augmenting bone repair and fusion procedures of the foot and ankle. The time, cost and morbidity involved in obtaining autograft, however, are well documented and legitimate concerns remain surrounding this intervention. Endogenous human PDGF is chemotactic and mitogenic for osteoblasts and undifferentiated osteoprogenitor cells, and upregulates expression of cytokines necessary for osseous and soft tissue healing and regeneration. The BB isoform of PDGF, and the biosynthetic replica recombinant human PDGF-BB, is a key regulatory molecule in bone homeostasis, repair and regeneration. When combined with a ββ-tricalcium phosphate osteoconductive matrix, recombinant human PDGF-BB mitigates a number of problems associated with the use of autograft and, based on its preclinical performance and early clinical success, appears to be an equally effective and perhaps an even safer alternative to autograft for foot and ankle fusion (arthrodesis) procedures.